Diversidade taxonômica das assembleias fúngicas associadas às raízes de plantas de mangue - Maia, Amalia Kessia Nobre (2024)
Mangroves are coastal ecosystems located in tropical and subtropical regions around the world. These are areas with great ecological, economic and social relevance; because due to their high primary productivity, they provide various ecosystem services, essential for human support and coastal and marine environments. Furthermore, they are considered blue carbon sinks, making them one of the main nature-based strategies to mitigate the effects of climate change. Most of the functions that enable the existence of various ecosystem services in mangroves are mediated by microorganisms, such as nutrient recycling and mediation of biogeochemical cycles. Despite their importance, fungal components of mangroves are still little explored. Thus, the central objective of this work is to describe the structure and taxonomic diversity present in fungal communities associated with the roots of mangrove plants, in three different areas of a mangrove forest in the state of Ceará, using independent cultivation methods. Data collection took place in three areas of the mangrove of Pacoti River (CE) (PELD site Costa Semiárida do Brasil) with different distances from the mouth and in three different periods (rainy season, transition and dry period) of the year 2022. Soil and roots of Rhizophora mangle were collected to carry out analyzes physics and chemistry and DNA sequencing. The salinity varied between 1 and 40 and the temperature varied from 24.8 - 30.9 oC. The soil was classified as fine/very fine sand. The organic matter content varied from 16 to 180 g/kg. The pH ranged from 5.1 – 7.72. The moisture content was 22 – 75%. The pyritization content varied from 5 – 77%. 13 fungal phyla, 44 classes were found, 116 orders, 261 families and 423 genera. Ascomycota (mainly Eurotiomycetes, Sordariomycetes and Dothideomycetes), a group of unclassified fungi, Basidiomycota and Chytridiomycota were most diverse in the fungal microbiome. The diversity and composition of fungi were similar in the soil and rhizosphere, and the endosphere showed distinction. In areas 1 and 3, fungal assemblages were influenced by the amount of organic matter, moisture content, silt- clay, phosphorus, pyritic iron and pyritization content, and area 2 was associated with salinity and sand quantity. We observed a tendency for the fungal composition to be more conserved in both the rainy and dry seasons, and more variable in the transition between these two periods. Our results indicate that seasonal variations in the environment may play a crucial role in ecological interactions between fungal species, resulting in changes in community composition over time. This work was funded by the Brazilian Semiarid Coast Long-Term Ecological Research Program (PELD CSB) (No. 442337/2020-5 -CNPq/PEL-00177- 0005.01.00/21-FUNCAP), with a master's scholarship offered by the Coordination for the Improvement of Higher Education Personnel- Brazil (CAPES) - Financing Code 001.